2015
DOI: 10.11613/bm.2015.008
|View full text |Cite
|
Sign up to set email alerts
|

The use of S-Monovette is effective to reduce the burden of hemolysis in a large urban emergency department

Abstract: BackgroundDue to the high prevalence of hemolysis in specimens received from the emergency department (ED), several strategies have been proposed to improve sample quality, but none of these seem effective to overcome the problem. In a preliminary study we showed that the use of S-Monovette blood collection system was effective to lower the risk of hemolysis in venous blood samples collected from intravenous catheters. This study was hence aimed to verify whether the replacement of a conventional vacuum system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…Lippi et al compared the Becton Dickinson (BD) Vacutainer™ system against the Sarstedt system, in both vacuum and aspiration mode, in 20 healthy volunteers and showed that blood collection by vacuum, regardless of the vendor, increases hemolysis rates [9]. In two subsequent retrospective studies, Lippi et al as well as Goegebuer et al confirmed a reduction in hemolysis rates by the use of an aspiration system compared to a vacuum system [6][7][8]. Other investigators, focusing on blood collection through an IV-catheter, reported similar results [11,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lippi et al compared the Becton Dickinson (BD) Vacutainer™ system against the Sarstedt system, in both vacuum and aspiration mode, in 20 healthy volunteers and showed that blood collection by vacuum, regardless of the vendor, increases hemolysis rates [9]. In two subsequent retrospective studies, Lippi et al as well as Goegebuer et al confirmed a reduction in hemolysis rates by the use of an aspiration system compared to a vacuum system [6][7][8]. Other investigators, focusing on blood collection through an IV-catheter, reported similar results [11,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Circumstances leading to in-vitro hemolysis are various and can be found in different process steps of specimen handling, including phlebotomy, transport, intra-laboratory processing or storage [4]. One of these variables is the type of blood collection system in use [5][6][7][8]. Vacuum systems are known to increase the rate of hemolytic specimen compared to aspiration systems due to higher shear stress, subsequently leading to damage of red blood cells [7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In an observational study conducted in a large urban ED we previously showed that collecting blood by means of a closed system entailing manual aspiration of blood instead of using conventional evacuated systems was effective to cut-down by nearly half the rate of hemolysis (i.e., from 4.41% to 2.57%). 5 Therefore, the aim of this observational, real world, study was to verify whether long-term replacement of standard evacuated blood collection systems with closed system entailing manual aspiration of blood (SMonovette, Sarstedt AG & Co., Nümbrecht, Germany) may be really effective to reduce the burden of spurious hemolysis. After an appropriate period of training, starting from June 1 st 2014 blood started to be collected only using S-Monovette blood tubes in aspiration mode.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed description of this device has been provided elsewhere. 5 In the local laboratory, all serum samples are systematically screened for hemolysis after centrifugation by photometrical assessment on Beckman Coulter AU5800 (Beckman Coulter Inc., Brea, CA, USA). The analyzer provides a semi-quantitative measure of hemolysis from (0 to 5 g/L) as hemolysis index (HI) by means of bichromatic readings at 410/480 and 600/800 nm.…”
Section: Introductionmentioning
confidence: 99%